Phytochemical Screening, Cytotoxic Activity, and Proximate Analysis of Split Gill Mushroom (Schizophyllum commune) - Acanto, Ricky; Cuaderes, Van Helen; Gomoto, Priscila (JPAIR Multidisciplinary Research, 2022)
Mushrooms play an essential role in the ecosystem and have provided humans with numerous benefits in terms of food and medicinal sources. The study was conducted to determine the phytochemical constituents, cytotoxic activity, and proximate analysis of a widespread mushroom in the region, Schizophyllum commune. Qualitative phytochemical analysis and cytotoxic activity of the ethanolic extract were conducted using the test tube method and brine shrimp lethality assay (BSLA). Proximate analysis was carried out using the standards the Association of Analytical Chemists set. Results revealed the presence of saponin, tannins, alkaloids, flavonoids, terpenoids, proteins, and carbohydrates. The linear regression analysis showed that the extracts exhibited a highly cytotoxic activity on brine shrimp with an LC50 value of 55.64 ppm. The cytotoxicity of the extract is mainly attributed to its phytochemical content. Proximate analysis revealed that the sample was composed primarily of moisture with high protein and low-fat content levels. Results support that S. commune is a good protein source and a healthy diet choice. The study may serve for further ethnobotanical, nutritional, and pharmacological studies.